Using Manipulative Media in Improving Students' Abilities in Operations to Calculate The Addition of Integers In Madrasah - Feriska Listrianti; Hasan Baharun; Sugiannoor; Nur Indah Wati (ZAHRA: Research and Tought Elementary School of Islam Journal, 2022)
This study aims to analyze the implementation of manipulative media using playing cards to improve the ability of arithmetic operations to add integers to students in madrasah. This research uses a qualitative case study approach. The data were obtained from interviews, observations, and documentation. Data analysis is carried out: data collection, reduction, data display, and conclusions. The results showed that the application of manipulative media at Madrasah Ibtidaiyah Al-Hanafiyah Kotaanyar went through three steps: preparing playing cards, conveying the rules of the game, and starting the game. The students' numeracy skills increased from the manipulative media application, and the average score evidenced this before applying the media to 55.38. After learning, the result is 87.31. This study provides implications about the importance of learning design that teachers must carry out by utilizing various kinds of media and learning resources around them.